2014
DOI: 10.1515/zfsoz-2014-0204
|View full text |Cite
|
Sign up to set email alerts
|

Pendelentfernung, Lebenszufriedenheit und Entlohnung / Commuting Distance, Life Satisfaction, and Wages

Abstract: ZusammenfassungDer Beitrag thematisiert den Einfluss der Pendelmobilität auf die allgemeine Lebenszufriedenheit. Zur genauen Beurteilung der Mobilitätseffekte prüfen die Analysen zudem den Effekt der Pendelentfernung auf das Einkommen sowie die Zufriedenheit mit der Wohnung und der beruflichen Situation. Die Untersuchung der Zusammenhänge beruht auf Längsschnittdaten des Sozio-oekonomischen Panels (SOEP) von 1998-2009 und den Indikatoren und Karten zur Raum- und Stadtentwicklung (INKAR). Fixed-Effects-Modelle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…Moreover, they demonstrated that commuting was characterized by rather low levels of positive effect, with a simultaneous fairly high negative effect. Similar findings were observed in another study investigating the commuting situation, salary, and life satisfaction [ 4 ]. In this work, commuting was negatively associated with overall life satisfaction but had no effect on the domains of life satisfaction, work and family.…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…Moreover, they demonstrated that commuting was characterized by rather low levels of positive effect, with a simultaneous fairly high negative effect. Similar findings were observed in another study investigating the commuting situation, salary, and life satisfaction [ 4 ]. In this work, commuting was negatively associated with overall life satisfaction but had no effect on the domains of life satisfaction, work and family.…”
Section: Introductionsupporting
confidence: 90%
“…The association between life satisfaction and commuting [ 4 , 15 , 16 , 18 ] was also investigated. For two areas of life satisfaction, namely income and lodging, significant results were found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Europe (EU25), most common are daily commuting times between 16 and 30 min (Vandenbrande 2006, p. 61). A study on the effects of commuting on life satisfaction in Germany revealed that for the majority of the employees the commuting distances are below 50 km, but mean distances increased from 1998 to 2009 for the majority of the employees (Pfaff 2014).…”
Section: Commutingmentioning
confidence: 99%
“…As is the case with residential relocations, also commuting is likely to affect partnerships positively or negatively. Although commuting has positive effects on income (Pfaff 2014), it involves also financial and psychic costs and is time consuming (Stutzer and Frey 2008). This might have a negative effect on the quality of partnerships and family relations.…”
Section: Interdependencies Between Partnership or Family Events Residential Relocations And Housing: Theoretical Perspectivesmentioning
confidence: 99%